REAL ESTATE MARKET IN ISLAMIC HISTORY TO MODERN ERA: THE ORIGIN AND EVOLUTION OF HOUSING SPECULATION - Mohd Razif, Nor Fahimah; Ab Halim, Asyiqin; Samsulkamal, Noor Sakinah; Abdul Wahab, Mazni (Journal of Al-Tamaddun, 2017)
Speculation is a contemporary financial term that was not used or discussed by classical Muslim scholars in the past. Speculation represents the significant risk of losing most or all of the capital in the pursuit of substantial profit. This study reviews the history and the development of real estate transactions that are profitable to the extent of creating speculative activity in the current financial world. This study reviews the history and development of real estate transactions that are profitable to the extent of creating speculative activity in the current financial world. This study traces the timeline of speculation in the real estate market from the era of Prophet Muhammad (PBUH) till today. To achieve the objective, this qualitative study collected the data needed through library research and interviews. Next, the data was analysed using the content analysis method. This descriptive research is timely in Malaysia given the soaring prices of housing and its growth into a significant area for investment.